Modelagem molecular por homologia e estudos de Docking molecular de potenciais alvos terapêuticos para Doença de Chagas - Souza, Alessandra Mendonça Teles de (2011)
The development of new drugs against Trypanosoma cruzi is still needed since the only drugs used to treat cause serious side effects. Naphthoquinones derivatives β-lapachone and oxiran-alfa-lapachone have high trypanocidal activity and act on different targets in the parasite. With the aim of obtaining parameters that influence the activity profile of these derivatives, computational techniques were used to study the interaction between protease inhibitors and oligopeptidase B and cruzain. In the first part of this work models of oligopeptidase B were built by homology modeling. Due to the low identity with the template 2BKL, models were constructed from alignments performed in ClustalW and 3D-coffee while were used SWISS-MODEL and Modeller programs to obtain three-dimensional structure. After the models validation, the model obtained from SWISS-MODEL and the alignment with ClustalW yielded better results, so it was selected for use in molecular docking studies. In the second part of this work, we studied molecular docking of β- lapachone and oxiran-alfa-lapachone in the active site of cruzain and oligopeptidase B. Studies of molecular docking in the active site of cruzain showed that β-lapachone, E64, a standard cysteine protease inhibitor, are involved in hydrogen bonds and interact hydrophobically with residues of the S1 sub-site, important for the specificity of the enzyme, justifying the inhibitory activity, while the oxiran-alfa lapachone does not participate in important interactions. The results of molecular docking in the active site of oligopeptidase B indicated that the oxiran-alfa-lapachone is located near the catalytic triad of the enzyme. The analysis of the complex showed that it participates in two hydrogen bonds with residues ARG649 and TYR481 corroborate the trypanocidal activity, and guide the oxiran ring with the SER562 the catalytic triad, indicating a possible nucleophilic attack (irreversible inhibition). The oligopeptidase B enzymes do not have homologues in humans, therefore is a potential target in studies of new drugs with trypanocidal activity. Thus, based on tests carried out and jointly with data obtained from the literature of oligopeptidase B inhibitors, 8 new derivatives of oxiran-alfa-lapachone were proposed based on molecular hybridization in order to increase the surface contact with the active site through hydrophobic interactions and salt bridges, as described in the literature as important for the inhibition of serine proteases.